PENGARUH BUDAYA ORGANISASI, KEDISIPLINAN, GAYA KEPEMIMPINAN TRANSFORMASIONAL, DAN GAYA KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA PEGAWAI (Studi pada Dinas Perindustrian, Perdagangan, Koperasi dan UKM Kab.Batang) - Teguh Aji Wibowo, 15.05.51.0058; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2019)
This study aims to analyze the influence of organizational culture, discipline, transformational leadership style and transactional leadership style on the performance of the employees of the Department of Industry, Trade, Cooperatives and SMEs. Stem. The population in this study were all District Office of Industry, Trade, Cooperatives and Small and Medium Enterprises. The criteria referred to in the use of purposive sampling technique this research are employees who have at least high school education. Based on these criteria, a sample of 68 employees was obtained. The analytical tool used is the test of validity, reliability, and multiple linear regression. The results of the analysis can be concluded that: Organizational culture has a positive and significant effect on the performance of employees of Disperindagkop and UKM Batang Regency. Discipline has a positive and significant effect on the performance of Disperindagkop And UKM employees in Batang Regency. Transformational leadership style has a positive and significant effect on the performance of employees of Disperindagkop and UKM Batang Regency. Transactional leadership style has a positive and significant effect on the performance of Disperindagkop and UKM employees in Batang Regency